Premature cystic lesions in shoulders of elite junior javelin and volleyball athletes: a comparative evaluation using 3.0 Tesla MRI - Beitzel, K.; Beitzel, K. I.; Zandt, J. F.; Buchmann, S.; Schwirtz, A.; Imhoff, A. B.; Reiser, M.; Brucker, P. U. (Journal of Shoulder and Elbow Surgery, 2013)
The purpose of this study was to evaluate clinical and magnetic resonance imaging (MRI) findings in the shoulders of high performance competitive junior javelin athletes and volleyball players. The hypothesis was that structural lesions already exist in young and asymptomatic overhead athletes.